Kecemasan Tokoh dalam Ranah 3 Warna Karya Ahmad Fuadi Kajian Psikologi Sastra - Annisauf Fadlilah Khoiri; Muhammad Rapi Tang; Hajrah Hajrah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The novel Ranah 3 Warna by Ahmad Fuadi discusses a lot about anxiety that is associated with Sigmund Freud's theory about personality dynamics in the form of anxiety. The discussion related to reality anxiety, neurotic anxiety and moral anxiety is interesting to study because there are still many people who experience anxiety but do not know the type of anxiety they are experiencing as is the case in the novel Ranah 3 Warna, describe the form of reality anxiety in the Anak Nusantara serial novel by Ahmad Fuadi, describe the form of neurotic anxiety in the novel Ranah 3 Warna by Ahmad Fuadi, describe the form of moral anxiety in the novel Ranah 3 Warna by Ahmad Fuadi. The method used in this study is a qualitative descriptive method. The data collection techniques used are documentation, reading techniques and note-taking techniques. Of the several forms of anxiety found in the novel, the words "anxious, afraid, worried" are very often used because the content of the novel is about the anxiety experienced by a man as the main character named Alif Fikri. The results of this study show the form of anxiety in three forms of anxiety, namely, reality anxiety, neurotic anxiety and moral anxiety. Based on the three forms of anxiety, it was found that the main character named Alif Fikri is a boy who is diligent, smart, loyal to friends, never gives up, trustworthy, ambitious and obedient to his parents. In the novel, there are many things related to anxiety starting from when Alif takes the exam, when his father is sick until he dies, when he takes part in a competition, when he takes part in a student exchange to Canada, and when he writes articles to be published in print media.